Risk for suicide nursing diagnosis and its related risk factors, in psychiatric settings: A descriptive study - Babak Saatchi; Taraneh Taghavi Larijani (Wiley, 2019)
Abstract Aim To assess the frequency of risk for suicide nursing diagnosis and its related risk factors, in the nursing care provided in psychiatric settings. Design This is a descriptive study. Methods The samples were the documented nursing reports. These reports were evaluated and analysed in terms of using the NANDA‐I risk for suicide nursing diagnosis and the risk factors related to this diagnosis. Results From the 1,440 reports that were reviewed, 10 nursing diagnoses and 478 risk factors, were identified. Based on the results of this study, risk for suicide is used at a very low level in psychiatric settings, while, considerable number of suicide's risk factors are still existing in these settings.